Effects of feed particle size distribution and chemical properties on roller press performance and comminution efficiency at plants 7 and 8 of PT Indocement Tunggal Prakarsa, Tbk - Mubarokah Nuriaini Dewi; Dwi Qurningsih; Samuel Armawan Sandi; Dody Guntama; Lukman Nulhakim; Lubena Lubena; Irma Agustin (Jurnal Polimesin, 2025)
Roller press is a comminution machine that works based on contact force and compression force at high pressure. Several operational constraints, such as hydraulic pressure, can cause the roller press feed to malfunction, leading to performance degradation. This study aims to analyze the effect of material feed characteristics on roller press performance in the finish mill unit of PT. Indocement Tunggal Prakarsa, Tbk. The methods used include Particle Size Distribution (PSD) analysis, free lime test, tricalcium silicate (C3S), and Work Index (WI) testing on samples from clinker plant 7 (P7) and plant 8 (P8). Roller press operational parameters hydraulic pressure, and grinding pressure, were analyzed to spread the impact of particle size distribution on comminution efficiency. The results showed that optimal roller press performance was achieved when the PSD material was evenly distributed with f80 of 12.98 mm and a reduction ratio of 8.16. The specific grinding power required was 5.33 N/mmÂ² with a power consumption of 6.92 kWh/t. In addition, clinker with C3S content of 62.53% and free lime of 1.25% had better grind-ability, with WI value of 12.90 kWh/t, which contributed to a comminution efficiency of 12.50%. The conclusion of this study is that the particle size distribution of feed material greatly affects the operational parameters of roller press and energy efficiency. Material with more even size distribution and better grind-ability results in more effective comminution performance and lower energy consumption, which has implications for improving the efficiency of grinding process in the cement industry.